Drought test resistance of maize varieties through PEG 6000. Issue 1 (January 2021) - Bukhari, B; Sabaruddin, Z; Sufardi, S; Syafruddin, S
Abstract: Abstracs. The germination phase is a very critical time for corn plants against water stress. Corn resistance to water stress in this phase is very different between cultivars. This initial test has been carried out in the Laboratory to determine the resistance level of some varieties of corn to water stress during the germination phase by using Poly Ethylene Glycol (PEG) 6000. There are nine corn varieties tested at three levels of PEG 6000 concentration of 0 % (0.00 MPa), 10 % (-0.19 MPa), and 20 % (-0.67 MPa). The experiment used a completely randomized 9 × 3 factorial design with 2 replications. The nine varieties tested were: Anoman 1 (V1 ), Lamuru (V2 ), Gumarang (V3 ), Srikandi Kuning (V4 ), Sukmaraga (V5 ), Bisma (V6 ), Arjuna (V7 )), Lagaligo varieties (V8 ), and NK-Jumbo varieties (V9 ). Selection of maize varieties on water stress during the germination phase of 9 selected varieties into 3 varieties consisting of one tolerant variety, one moderately tolerant variety and one sensitive variety through prediction of a PEG 6000 osmoticum solution in the germination phase. The experimental results showed that the concentration of PEG 6000 affected the response of nine corn varieties to germination and seed vigor. The most tolerant (resistant) corn varieties are NK-Jumbo (V9 ) and the moderately resistant varieties (medium) are Srikandi Kuning (V4 ) while the intolerant (sensitive) varieties are Lamuru (V2 ).